A= $\frac{4}{31.7}$+$\frac{6}{7.41}$+$\frac{9}{10.41}$+$\frac{7}{10.57}$
\Rightarrow $\frac{A}{5}$=$\frac{4}{31.7.5}$+$\frac{6}{5.7.41}$+$\frac{9}{10.5.41}$+$\frac{7}{10.5.57}$
\Rightarrow $\frac{A}{5}$=$\frac{4}{31.35}$+$\frac{6}{35.41}$+$\frac{9}{50.41}$+$\frac{7}{50.57}$
\Rightarrow $\frac{A}{5}$=$\frac{1}{31}$-$\frac{1}{35}$+$\frac{1}{35}$-$\frac{1}{41}$+$\frac{1}{41}$-$\frac{1}{50}$+$\frac{1}{50}$-$\frac{1}{57}$
\Rightarrow $\frac{A}{5}$=$\frac{1}{31}$-$\frac{1}{57}$
\Rightarrow A= 5($\frac{1}{31}$-$\frac{1}{57}$)
B= $\frac{7}{19.31}$+$\frac{5}{19.43}$+$\frac{3}{23.43}$+$\frac{11}{23.57}$
\Rightarrow $\frac{B}{2}$=$\frac{7}{2.19.31}$+$\frac{5}{2.19.43}$+$\frac{3}{2.23.43}$+$\frac{11}{2.23.57}$
\Rightarrow $\frac{B}{2}$=$\frac{7}{38.31}$+$\frac{5}{38.43}$+$\frac{3}{46.43}$+$\frac{11}{46.57}$
........(làm tuơng tự câu A) \Rightarrow B=2($\frac{1}{31}$-$\frac{1}{.57}$)
\Rightarrow$\frac{A}{B}$= $\frac{5(\frac{1}{31}-\frac{1}{57})}{2(\frac{1}{31}-\frac{1}{57})}$=$\frac{5}{2}$